Blueprint- MR I-casing / Hood Romel Miyasin@Yassin...[et al.] - Miyasin@Yassin, Hood Romel; Mijim, Jimmy; Fadzli, Julia; Hassan, Noryhati (2019)
Mr. I-Casing Company is a company that produce life-changing phone case that changes the ways people use phone bumper. Innovated, improvise and continuously research as well as develop new alternative ways to satisfy customers' need. Mr. I-Casing is the name of the product, an intelligent casing design has a small compartment at the backside that can fit a small credit card size item. This small-compartment had beptfcarefully design and attach at the centre of the casing to make it convenience to place standard size card.The company has a simple lean organization structure. The head is tea by a CEO. Under the CEO, there are three different departments that have special function of each. There are marketing department, operation department, and financial department. The current target market is the student of Universiti Teknologi Mara (UiTM) Shah Alam with a potential customer of 160,957. Marketing plan including using pricing strategy, mass promotion strategy, and distribution centre strategy. The potential competitor had been identified to be the company that produce mass phone casing for smartphone and the one who produced card compartment wallet. The operation is involving the product development is to innovate based on customer need, imply planning and control that including cost determination, build prototype, testing, and refine the design. Next, process of gathering data into a physical product and launch into business market. Financial planning is based of expenditure, revenue, and gross profit.